Pengaruh Kepemimpinan Spritual dan Motivasi Spritual Terhadap Kualitas Pelayanan Syariah Grand Permata Hati Banda Aceh - Mazas, Ichsan Akmal; Fitri, Aida; Harbiyah G, Harbiyah G (Center for Research and Community Service (LPPM) University of Abulyatama, 2025)
This study aims to examine the influence of spiritual leadership and spiritual motivation on the quality of Sharia-compliant services at Grand Permata Hati Hotel. The method used in this research is a quantitative approach aimed at determining the influence or relationship between two or more variables in a study. The sample size for this research consists of 100 respondents. The sampling technique used for data collection in this study was non-probability sampling, specifically employing accidental sampling. Research data were gathered through questionnaires and documentation studies. Hypothesis testing was conducted using multiple linear regression analysis, the F-test (simultaneous testing), and the t-test (partial testing) to examine the effect of independent variables on the dependent variable with a 95% confidence level (α = 0.05). The research findings indicate that at a 5% significance level, the F-statistic value (43.403) exceeds the F-critical value (2.704), demonstrating that spiritual leadership and spiritual motivation simultaneously influence the quality of sharia services at Hotel Grand Permata Hati Banda Aceh. Additionally, partial testing shows all variables accept Ha and reject Ho, as the T-statistic values exceed the T-critical values. Thus, the study implies that spiritual leadership and motivation significantly impact the quality of sharia services at Hotel Grand Permata Hati Banda Aceh.